Enhancing Solubility and Dissolution of Olanzapine by Spray Drying Using β- Cyclodextrin Polymer - Mudit Dixit, R. Narayana Charyulu, Anupama Shetty, Narayana Charyalu, Meghana Rao, Pallavi Bengre, Sharin Thomas (Journal of Applied Pharmaceutical Science, 2014)
Olanzapine, an antipsychotic agent, exhibits poor water solubility, dissolution and flow properties. Thus, the aim of the present study was to improve the solubility and dissolution rate of Olanzapine by preparing microspheres by spray drying technique using β-cyclodextrin. Olanzapine Microspheres containing different ratios of β-cyclodextrin were produced by spray drying using Propanol and water (50:50) as solvent system to enhance solubility and dissolution rate. The prepared formulations containing different ratios of drug and β-cyclodextrin were evaluated for solubility and in-vitro dissolution. The prepared formulations were characterized by DSC, FT-IR, XRD and SEM. Dissolution profile of the prepared spray dried microspheres was compared with its physical mixture and pure sample. Spray dried microspheres exhibited decreased crystallinity. The solubility of microspheres containing Olanzapine and β-cyclodextrin (1:3w/w) exhibited tenfold increases than the commercial Olanzapine and dissolution of same ratio microsphere showed 99 % release in 20 min. while same composition in physical mixture showed 37% release in 20 min. Consequently, from the above result it can be concluded that spray dried microspheres of Olanzapine is a useful technique to improve the solubility and dissolution of poor water soluble drug like Olanzapine.
Keywords: Spray drying, microspheres, Olanzapine, &beta; -cyclodextrin, solubility, dissolution.